Strategi Kesantunan Tuturan Positif dan Negatif pada Komik Nawadir Juha Li Al-Athfal - Fikri Fikri; Dyta Septiyatik (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2023)
This study aims to describe the form of politeness in the comic Nawadir Juha Li al ethical. This research is qualitative descriptive research with a type of literature study. The data collection method used in this study is the listening method with note-taking techniques by recording utterances containing positive and negative politeness based on Brown and Levinson's theory. This research was carried out in three stages, first providing data; Data Analysis Stages; and data presentation stage. The results showed that of the ten negative politeness strategies according to Brown and Levinson, there were 4 strategies found in the NJLA comics, namely (1) apologizing, (2) Not giving to do act, (3) Dissociating the requester from the impingement, (4) State clearly that the interlocutor is very valuable. Of the fifteen positive politeness strategies according to Brown and Levinson, there are 7 strategies found in NJLA comics, namely (1) attending to the address, (2) exaggerating, (3) avoiding disagreement, (4) being optimistic, (5) claiming that whatever H wants, (6) asking for reasons, (7) Satisfying some of H's wants Abstrak Penelitian ini bertujuan untuk mendeskripsikan bentuk kesantunan berbahasa dalam komik Nawadir Juha Li al athfal. Penelitian ini termasuk penelitian deskriptif kualitatif dengan jenis studi kepustakaan. Metode pengumpulan data yang digunakan pada penelitian ini adalah metode simak dengan teknik catat dengan cara mencatat tuturan yang mengandung kesantunan positif dan negatif berdasarkan teori Brown dan Levinson. Penelitian ini dilaksanakan dalam tiga tahapan, pertama penyediaan data; tahap analisis data; dan tahap penyajian data. Hasil penelitian menunjukkan bahwa dari sepuluh strategi kesantunan negatif menurut Brown dan Levinson terdapat 4 strategi yang terdapat pada komik NJLA, yaitu (1) apologizing, (2) Not giving to do act, (3) Dissociating the requester from the impingement, (4) State clearly that the interlocutor are very valuable. Dari lima belas strategi kesantunan positif menurut Brown dan Levinson terdapat 7 strategi yang terdapat pada komik NJLA, yaitu (1) attending the address,(2) exaggerating, (3) avoiding disagreement, (4) being optimistic, (5) claim that whatever H wants, (6) asking for reason, (7) Satisfying some of H’s wants.